Identification of Plant Diversity for Natural Dyes in the Making of Kodi Balaghar Ikat Weaving - Kaleka, Yohanis Umbu; Kerans, Geterudis; Nura, Farmiany Scolastika (Universitas Lambung Mangkurat, 2024)
The study aims to examine more about the kinds of plants that are used as natural dyes, how they are classified and described, what organs are used, what colours are generated, how to combine different plant types, and how to create patterns on Kodi Balaghar ikat cloth. The researchers employed a qualitative methodology, with observation, interviews, exploration, and documentation as the primary data-gathering modes. The results of this study show that there are nine types of plants used as natural dyes, namely: Indigo leaves (Indigofera tinctoria L.), Kesambi wood (Scheilchera oleosa), Kepuh (Sterculia foetida L.), Pule (Alstonia scholaris), Poison Sumac (Toxicodendron radicans), Yellow wood (Arcangelisia flava L.), Noni (Morinda citrifolia L.), Black rice (Oryza sativa L.), Rice (Oryza sativa L.). Descriptions of each type of natural dye plant have been made in full. The plant organs used are roots, bark, fruit, and leaves. The coloring process includes pounding, mixing with water, and soaking. The resulting colors are dark blue and black. The motifs produced include Kris flowers and buffalo eyes.